Experience with long-term use of certolizumab pegol (Cimzia) - Karine Arnoldovna Lytkina; G P Arutyunov (Современная ревматология)
Objective: to establish whether long-term combination therapy with a tumor necrosis factor (TNF) α inhibitor and a disease-modifying antirheumatic drug (DMARD) (methotrexate – MTX) may lead to sustained rheumatoid arthritis (RA) remission and its maintenance even after discontinuation of genetically engineered biological agents (GEBA). Subjects and methods. Moscow City Clinical Hospital Four had been following up 5 patients (4 women and 1 man) receiving certolizumab pegol (CZP, Cimzia) since 2005. Their treatment was performed in the CDP 879-027/28 study until August 2011; thereafter the patients continued to receive the drug at the department until February 2011. The patients’ mean age was 49.2±8.58 years; the average duration of RA was 4.4±2.3 years. The reason for using the medicament was ineffective previous standard DMARD therapy (sulfasalazine, leflunomide; when using CZP, all the patients took MTXin a dose of 10-15 mg/week; 2 patients had it in combination with prednisolone 5-7.5 mg/day). In all the patients, the disease activity remained high (mean DAS28, 6.33±0.52). Quality of life (QL) was also assessed using overall HAQ, EQ-5 questionnaires. The mean EQ-5D and HAQ QL scores were 50±7.9 and 1.825±0.17, respectively. The patients received either CZP 400 or 200 mg, or placebo in a blind study in October to December 2005; in an open-label study they took 400 mg CZP subcutaneously once two weeks since 2006 and 200 mg of this agent subcutaneously once two weeks (the dose was reduced according to the protocol after data on the efficiency of this dosage regimen were accumulated) since February 2008. Results. By the end of CZP treatment, 3 patients achieved sustained (1-year or more) remission (DAS28<2.6); 2 patients had low disease activity (DAS28<3.2), as confirmed by QL indicators according to the HAQ and EQ-5D questionnaires. It was decided that 3 patients would not resume GEBA therapy. They continued to take MTX 12.5-15 mg/week as DMARD therapy. One patient with a maximum DAS28 score of 3.16 by the end of the protocol continued to be treated with CZP (200 mg subcutaneously once two weekly). Another female patient with moderate RA activity at the end of therapy herself completed the treatment with a TNF-α inhibitor.  Following a year, 2 patients remained in sustained RA remission and did not need a GEBA. RA activity increased in a female patient who had stopped treatment; she was recommended to resume therapy with the TNF-α inhibitor. Another female patient was stated to have a low RA activity and her follow-up was continued Conclusion. The findings are evidence in favor of the fact that long-term combination therapy with a TNF-α inhibitor in combination with MTX may lead to not only sustained RA remission, but also its maintenance even after a GEBA was discontinued. The use of CZP for 6.5 years induced remission and promoted stability in some patients during a year after drug discontinuation.